2012
DOI: 10.2341/11-344-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Diamine Fluoride on Microtensile Bond Strength to Dentin

Abstract: The aim of this in vitro study was to investigate the effect of the cariostatic and preventive agent silver diamine fluoride (SDF) on the microtensile bond strength of resin composite to dentin. Forty-two caries-free, extracted molars were flattened occlusally and apically using a diamond saw, and the exposed occlusal dentin was polished with a series of silicon carbide papers, all under water irrigation. The teeth were then randomly divided into six groups of seven teeth each that were treated as follows: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 17 publications
2
61
1
Order By: Relevance
“…The traditional approach of managing cavitated carious lesions is to drill and fill, which refers to mechanically removing the soft and bacteria‐infected dentine before filling the cavity with a proper restorative material. It is still reasonable to conduct the excavation because infected dentine is highly demineralised and physiologically not remineralisable based on the current evidence. Nevertheless, there is evidence showing that removal of soft carious lesions may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional approach of managing cavitated carious lesions is to drill and fill, which refers to mechanically removing the soft and bacteria‐infected dentine before filling the cavity with a proper restorative material. It is still reasonable to conduct the excavation because infected dentine is highly demineralised and physiologically not remineralisable based on the current evidence. Nevertheless, there is evidence showing that removal of soft carious lesions may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries, defined as a localised, pathological process with multiple factors, softening dental hard tissues and proceeding to the formation of cavities, continues to be a prevalent disease all over the world. In recent years, the development of restorative materials and advancement in our conception of the caries process have created the capability to practice in consideration of a minimally invasive dentistry philosophy. It requires performing management with as little tissue loss as possible and without causing any destruction to the adjacent healthy tooth tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies also showed the success of SDF in preventing and arresting dental caries [11,12]. A laboratory study found that the bond strength of restorations to dentine was not adversely affected by SDF using resin-based adhesives [13]. The application of SDF under GIC restorations has been demonstrated to produce a promising pulpal response and be effective in facilitating the formation of reparative dentine [14].…”
Section: Introductionmentioning
confidence: 99%
“…With this result, it can be concluded that it is preferable to use an adhesive with an etching technique and rinsing instead of one self-etch prior to treatment with diamine silver fluoride. [8] Regarding effects on the resistance of tooth bond restoration, Knight et al conducted an in-vitro study in order to compare the strength of adhesion of glass ionomer cement on dentin surfaces. Tooth surfaces were treated with diamine silver fluoride/iodide of potassium and compared to untreated dentin.…”
Section: Discussionmentioning
confidence: 99%